Identifying enhancement of double slope solar still performance by adding water cooling to walls - Ismail, Nova Risdiyanto; Suwandono, Purbo; Hermawan, Dadang; Anggraeni, Frida Dwi (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this research is a double-slope solar still with the addition of water cooling on the wall (DSSS.WCW). The issue with solar stills is that the temperature of the cover glass is quite high, which consequently reduces the rate of evaporation. Methods to reduce the cover glass temperature involve water cooling, by flowing water and spraying it onto the cover glass. Both of these methods have been shown to reduce the temperature of the cover glass, but they still require additional energy and can decrease the solar radiation energy received by the absorber plate. This research proposes using a water cooling method on the wall that does not require additional energy and can prevent a reduction in the solar radiation energy received by the absorber plate. Experimental and theoretical research was conducted to study the effect of using DSSS.WCW. The results showed a 13.48 % reduction in the cover glass temperature, consequently increasing the temperature difference between the fins and the cover glass by 9.82 °C. The increase in temperature difference resulted in a 13.82 % increase in freshwater productivity theoretically by 2.80 kg/hour and a 13.10 % increase experimentally for the DSSS.WCW by 2.58 kg/hour. In addition, there was a theoretical increase in energy efficiency of 22.29 % and an experimental increase of 22.82 %, along with an increase in exergy efficiency of 15.71 %. The implementation of water cooling on the wall has been shown to enhance the efficiency of the double-slope solar still. In addition, the water cooling method on the wall does not reduce the solar radiation energy that can be received by the absorber plate and does not require additional energy. The results of this research can be applied in remote islands in Indonesia, particularly during the dry season